Neuro-Symbolic Generative Frameworks for Explainable Artificial Intelligence in Complex Decision Systems (Journal of Generative Intelligence E: 3117-6429 P: 3117-6437, 2025)
Artificial intelligence has achieved superhuman performance in domains such as medical diagnosis, financial forecasting, autonomous driving, and legal analytics. However, the lack of interpretability in deep learning limits adoption in safety-critical and regulated environments. Neuro-symbolic generative frameworks attempt to bridge symbolic reasoning's transparency with the representational power of neural networks. This research explores architecture design, reasoning pipelines, knowledge grounding, generative explanation synthesis, symbolic constraint integration, and real-world deployment challenges. The paper proposes a unified neuro-symbolic generative model called Neuro-Symbolic Explainable Generator (NSEG), integrating latent neuro-reasoning, symbolic knowledge graphs, rule-based verification, and natural language explanation synthesis. Experimental evaluations across healthcare, finance, and autonomous decision benchmarks show that neuro-symbolic generation achieves up to 67% improvement in explanation faithfulness, 41% reduction in reasoning hallucination, and 23% higher decision traceability compared to transformer-only explainability baselines. Comprehensive analysis, ethical implications, limitations, and implementation guidelines for industry adoption are presented.